Let's denote Andrea's current age as \( a - 6 \), since she is 6 years younger than Tony, who is \( a \) years old.
In two years, Tony's age will be \( a + 2 \) and Andrea's age will be \( (a - 6) + 2 = a - 4 \).
According to the problem, in two years, Tony's age will be three times Andrea's age:
\[ a + 2 = 3(a - 4) \]
Now, let's look at the options provided:
A. \( a + 2 = 3(a - 6 + 2) \)
B. \( a + 2 = 3(a + 6 + 2) \)
C. \( a = 3(a + 2) \)
D. \( 3(a + 2) = a - 6 + 2 \)
Let's simplify option A to see if it matches with our derived equation: \[ 3(a - 6 + 2) = 3(a - 4) \quad \text{(which matches our derived equation)} \] So, option A is actually valid.
Now let's analyze the others:
- Option B is incorrect because it does not correctly represent Andrea's age.
- Option C is incorrect because it doesn’t reflect the relationship described in the problem.
- Option D is incorrect because it rearranges the terms inaccurately regarding ages.
The correct answer is:
A. \( a + 2 = 3(a - 6 + 2) \)